Carbon Dioxide Viscosity Modifier for Enhanced Oil Recovery EOR Application - Khadija Dakhila,; Azmi Mohamed, (AlQalam Journal of Medical and Applied Sciences, 2025)
This study focuses on a new approach to enhance the viscosity of supercritical CO2 (scCO2) for enhanced oil recovery EOR applications. Fluorinated surfactants have been synthesised and used as viscosity modifiers; however, there is no systematic studies have been carried out toward scCO2 viscosity enhancement, thus impeding the commercial developments. Here, metallosurfactant structure design was focused on anionic surfactant analogues of Aerosol -OT (sodium bis (2-ethylhexyl) sulfosuccinate). The metallosurfactants were synthesised with modification on the surfactant chain with the introduction of nickel (Ni2+) and manganese (Co2+) counter ions. Nuclear Magnetic Resonance (NMR) Spectroscopy, Elemental analysis (EA), UV-Visible Spectroscopy and High-Pressure Viscometer have investigated the metallosurfactant. The result shows that fluorination is a crucial factor influencing Aerosol-OT surfactant analogue compatibility with scCO2. The presence of fluorine in the metallosurfactant chemical structure gives rise to relative scCO2 viscosity. The results obtained are beneficial for CO2 studies in enhanced oil recovery applications.